1981
DOI: 10.1530/jrf.0.0620213
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of the oestrous cycle in cows and ewes after passive immunization with PGF antibodies

Abstract: Three cows and 2 sheep were passively immunized against prostaglandin (PG) F on Day 16 and Days 13-15 of the oestrous cycle respectively. The PGF antiplasma was raised in ovariectomized ewes against a PGF-2 alpha-bovine serum albumin complex and showed 100%, 12.5%, 0.3%, less than 0.05% and less than 0.01% cross-reactivity with PGF-2 alpha, PGE-2, PGA-2, PGB-2 and arachidonic acid, respectively. Control animals were given an equivalent amount of ovariectomized ewe plasma. In all passively immunized animals the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In non-pregnant cows and sheep, there is evidence that PGF-2a of uterine origin is the physiological luteolysin (Fairclough et al, 1981). Towards the end of the oestrous cycle, therefore, increased oxytocin secretion is thought to trigger the production of uterine PGF-2a which then acts locally on the ipsilateral corpus luteum to bring about its regression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-pregnant cows and sheep, there is evidence that PGF-2a of uterine origin is the physiological luteolysin (Fairclough et al, 1981). Towards the end of the oestrous cycle, therefore, increased oxytocin secretion is thought to trigger the production of uterine PGF-2a which then acts locally on the ipsilateral corpus luteum to bring about its regression .…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro studies have shown that oxytocin stimulates the release of PGF-2a from uterine tissue (Roberts, McCracken, Gavagan & Soloff, 1976), while in-vivo experiments have demonstrated a temporal relationship between plasma levels of oxytocin-associated neurophysin I/II and the prostaglandin F metabolite (13,14-dihydro-15-ketoprostaglandin F) at the end of the oestrous cycle . The luteolytic role of prostaglandins has been repeatedly shown (Horton & Poyser, 1977;Fairclough, Smith & McGowan, 1981).…”
Section: Introductionmentioning
confidence: 98%
“…Prostaglandin F-2a has been proposed as the uterine luteolysin in numerous species including cattle (Horton & Poyser, 1976;Knickerbocker et al, 1988 Baird, 1976;Fairclough et al, 1981) and cattle (Fairclough et al, 1981;Chang et al 1987). In the present study, active immunization against PGF-2a extended the lifespan and function of corpora lutea anticipated to be short-lived.…”
Section: Discussionmentioning
confidence: 52%
“…Both active and passive immunization against PGF-2a lengthened the functional lifespan of corpora lutea in sheep (Scaramuzzi & Baird, 1976;Fairclough et al, 1981), guinea-pigs (Horton & Poyser, 1974;Poyser & Horton, 1975) and cattle (Fairclough et al, 1981;Chang et al, 1987). Therefore, the objective of this study was to determine whether active immunization of pre-partum and post-partum cows against PGF-2a would extend the lifespan and progesterone secretion of short-lived corpora lutea.…”
Section: Introductionmentioning
confidence: 99%
“…The smallest amount of progesterone that could be measuredwithprecision was0.15ng/mlserum. The intra-and inter-assay coefficients of variation for a plasma pool assayed on 16 consecutive occasions and containing progesterone at a concentration of 0.9 ng/ml were 9.6 and 10.9% respectively (Fairclough et al 1981).…”
Section: Timing Of Treatmentsmentioning
confidence: 95%